Delayed Modeling Approach to Forecast the Periodic Behavior of SARS-2 - Yu, Zhenhua; Sohail, Ayesha; Nutini, Alessandro; Arif, Robia (Frontiers in Molecular Biosciences, 2021)
The ongoing threat of Coronavirus is alarming. The key players of this virus are modeled mathematically during this research. The transmission rates are hypothesized, with the aid of epidemiological concepts and recent findings. The model reported is extended, by taking into account the delayed dynamics. Time delay reflects the fact that the dynamic behavior of transmission of the disease, at time $t$ depends not only on the state at time $t$ but also on the state in some period $τ$ before time $t$. The research presented in this manuscript will not only help in understanding the current threat of pandemic (SARS-2), but will also contribute in making precautionary measures and developing control strategies.